Regenerasi Pemerolehan Seni Lais di Padepokan Lais Pancawarna Kampung Sayang Desa Cibunar Kecamatan Cibatu Kabupaten Garut - Ayu Septiani; Asri Soraya Afsari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This paper aims to determine the existence and acquisition of Lais Art in Padepokan Lais Pancawarna. This paper uses ethnographic methods that refer to qualitative research. The data sources used are divided into two, namely primary data sources and secondary data sources. Primary data sources are data in the field through participant observation. Furthermore, for secondary data used library sources. The results of this study that Lais Art is a traditional art of Garut which is almost extinct in Garut. To preserve Lais Art, it uses three models of inheritance, namely upright inheritance, inherited from genetics, inherited inheritance, which is carried out with others through formal or normal education and horizontal inheritance, namely by training children or peers in the community. The conclusion is the need for cultural preservation, one of which is by inheriting culture to the younger generation as the nation's successors. Keywords: Model of Inheritance, Regeneration, Seni Lais